Acid and alkali resistant composite nanofiltration membrane, preparation method and application thereof

By introducing a polyurea-thiourea separation layer into the nanofiltration membrane, the problem of poor stability of existing nanofiltration membranes under acidic and alkaline conditions is solved, achieving high water permeability and acid permeability over a wide pH range, making it suitable for industrial wastewater treatment.

CN120961002BActive Publication Date: 2026-11-06CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410612635.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-16
Publication Date
2026-11-06
Estimated Expiration
2044-05-16

AI Technical Summary

Technical Problem

Existing nanofiltration membranes exhibit poor stability under acidic and alkaline conditions, low water flux, and limited acid and alkali permeability, thus restricting their application in the treatment of industrial waste acid or waste alkali.

Method used

Using polyurea-thiourea as the separation layer, a dense polyurea-thiourea separation layer is formed on the surface of the porous support layer through the interfacial polymerization reaction of polyamines, polyisocyanates and polyisothiocyanates, thereby improving the acid resistance, alkali resistance, water permeability and acid permeability of the nanofiltration membrane.

Benefits of technology

It operates stably within the pH range of 0-14, exhibiting high water permeability, acid permeability, and alkali permeability. It is suitable for treating industrial waste acid or waste alkaline water, and has excellent acid and alkali resistance and high water flux.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120961002B_ABST
    Figure CN120961002B_ABST
Patent Text Reader

Abstract

This invention relates to the field of membranes, and discloses an acid and alkali resistant composite nanofiltration membrane, its preparation method, and its applications. The composite nanofiltration membrane sequentially comprises a bottom layer, a porous support layer, and a polyurea-thiourea separation layer; the polyurea-thiourea separation layer includes structural units I derived from polyamines, structural units II derived from polyisocyanates, and structural units III derived from polyisothiocyanates; wherein structural units I and II are connected; and structural units III are connected. This composite nanofiltration membrane uses polyurea-thiourea as the separation layer, enabling it to possess excellent acid and alkali resistance while also exhibiting high water permeability, acid permeability, and alkali permeability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of membranes, and more specifically, to an acid and alkali resistant composite nanofiltration membrane, its preparation method, and its application. Background Technology

[0002] Nanofiltration is a pressure-driven filtration technology that separates materials. The nanofiltration membrane is the core of this technology, with a pore size ranging from a few nanometers. It can separate monovalent and polyvalent ions, and efficiently remove organic matter with a molecular weight in the range of 200–1000 Da. Due to its low operating pressure, low energy consumption, and high separation precision, nanofiltration membranes are widely used in freshwater softening, seawater softening, drinking water purification, water quality improvement, oil-water separation, wastewater treatment and recycling, as well as in the classification, purification, and concentration of chemical products such as dyes, antibiotics, peptides, and polysaccharides.

[0003] Currently, most commercial nanofiltration membranes are polyamide composite membranes, formed by the interfacial polymerization of polyamines and polyacrylamide chlorides on a porous support layer. Polyamide composite nanofiltration membranes have advantages such as high rejection rate and large water flux. However, due to the limitations of their molecular structure, the polyamide separation layer has a narrow pH tolerance range, maintaining good filtration performance only within the pH range of 2 to 12. When the pH of the feed solution exceeds this range, the polyamide molecular segments will hydrolyze, leading to a significant reduction in the separation performance of the nanofiltration membrane. Therefore, large quantities of waste acid or alkaline water generated in metallurgy, mining, printing and dyeing, textiles, and pharmaceutical industries cannot be treated using commercial polyamide nanofiltration membranes.

[0004] To address the issues of compliant discharge of industrial waste acid or alkaline wastewater and the resource recovery and utilization of acids and alkalis, foreign membrane companies have developed corresponding nanofiltration membrane products. Among them, KOCH's MPF series nanofiltration membranes are the most widely used, operating stably within a pH range of 0-14. GE's acid-resistant nanofiltration membrane, DuracidNF1812C, has a three-layer composite structure with a polysulfonamide separation layer that remains stable under 20% hydrochloric acid, sulfuric acid, and phosphoric acid conditions, and also remains stable at 70°C and 20% sulfuric acid concentration. Israel's AMS has developed acid- and alkali-resistant nanofiltration membranes. According to US9943811A1, this membrane uses cross-linked polyacrylonitrile as a porous support layer, produced through interfacial polymerization of polyamines and cyanuric chloride. Nitto Denko Hydranautics' HYDRACoRe series membranes exhibit excellent acid / alkali stability and have been applied in sugar decolorization and dyeing industries. The HYDRACoRe series membranes are also composite membranes, with the separation layer being sulfonated polyethersulfone ("HYDRACoRe70pHT acid and alkali resistant high temperature nanofiltration membrane for the recovery of alkali waste in sugar industry, Membrane Science and Technology, 32, 11-15, 2006").

[0005] Polyurea polymers possess excellent acid / alkali resistance. In 1975, Cadotte reported the preparation of a reverse osmosis membrane via interfacial polymerization of polyethyleneimine and toluene diisocyanate. However, the acid / alkali resistance of this material was not reported, nor were the separation and acid / alkali resistance properties of composite membranes made from isocyanates with other structures. CN113509893A discloses a nanofiltration membrane with a cross-linked polyurea structure as the separation layer and its application in acid / alkali treatment. This polyurea nanofiltration membrane exhibits excellent retention performance and stable acid / alkali stability. However, its low water flux and low acid / alkali permeability limit its application in acid / alkali purification and recovery.

[0006] Therefore, developing acid / alkali resistant nanofiltration membrane materials with high acid and alkali permeability has greater practical application value. Summary of the Invention

[0007] The purpose of this invention is to overcome the problems of low water flux and poor acid and alkali permeability of existing acid and alkali resistant nanofiltration membranes, and to provide an acid and alkali resistant composite nanofiltration membrane, its preparation method and application. The composite nanofiltration membrane uses polyurea-thiourea as the separation layer, so that the nanofiltration membrane has excellent acid and alkali resistance, while also having high water permeability, acid permeability and alkali permeability.

[0008] To achieve the above objectives, the first aspect of the present invention provides an acid and alkali resistant composite nanofiltration membrane, wherein the composite nanofiltration membrane comprises, in sequence, a bottom layer, a porous support layer, and a polyurea-thiourea separation layer;

[0009] The polyurea-thiourea separation layer includes structural unit I from polyamines, structural unit II from polyisocyanate compounds, and structural unit III from polyisothiocyanates;

[0010] Wherein, structural unit I and structural unit II are connected by connect;

[0011] The structural unit I and the structural unit III are connected by... connect.

[0012] A second aspect of the present invention provides a method for preparing an acid- and alkali-resistant composite nanofiltration membrane, wherein the preparation method includes the following steps:

[0013] S1. Prepare a porous support layer on the bottom layer;

[0014] S2. The membrane layer obtained in step S1 is first contacted with an aqueous phase containing polyamines, and then second contacted with an organic phase containing polyisocyanates and polyisothiocyanates. After heat treatment, the acid and alkali resistant composite nanofiltration membrane is obtained.

[0015] A third aspect of the present invention provides an acid- and alkali-resistant composite nanofiltration membrane prepared by the above-described preparation method.

[0016] The fourth aspect of this invention provides an application of the above-mentioned acid and alkali resistant composite nanofiltration membrane in the field of water treatment.

[0017] Through the above technical solutions, the acid and alkali resistant composite nanofiltration membrane, its preparation method, and its application provided by the present invention achieve the following beneficial effects:

[0018] The acid-alkali resistant composite nanofiltration membrane provided by this invention uses polyurea-thiourea as the separation layer, enabling the nanofiltration membrane to possess excellent acid and alkali resistance while also exhibiting high water permeability, acid permeability, and alkali permeability. Specifically, the acid-alkali resistant composite nanofiltration membrane provided by this invention can operate stably in aqueous solutions with pH = 0-14, possessing not only high water and alkali permeability but also strong acid / alkali resistance. Moreover, its preparation method is simple, making it highly promising for industrial applications.

[0019] In the preparation method of the acid and alkali resistant composite nanofiltration membrane provided by the present invention, the different reactivity of polyamine, polyisocyanate and polyisothiocyanate is utilized so that a dense polyurea-thiourea separation layer is formed on the surface of the porous support layer during the interfacial polymerization reaction of the three. This can significantly improve the water permeability and alkali permeability while ensuring the high salt rejection rate of the nanofiltration membrane. Attached Figure Description

[0020] Figure 1 The salt rejection rate and water flux of the composite nanofiltration membrane prepared in Example 1 vary with the soaking time in a 20 wt% HCl aqueous solution.

[0021] Figure 2 The salt rejection rate and water flux of the composite nanofiltration membrane prepared in Example 1 vary with the soaking time in a 20 wt% NaOH aqueous solution. Detailed Implementation

[0022] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0023] The first aspect of the present invention provides an acid and alkali resistant composite nanofiltration membrane, wherein the composite nanofiltration membrane comprises, in sequence, a bottom layer, a porous support layer and a polyurea-thiourea separation layer;

[0024] The polyurea-thiourea separation layer includes structural unit I from polyamines, structural unit II from polyisocyanate compounds, and structural unit III from polyisothiocyanates;

[0025] Wherein, structural unit I and structural unit II are connected by connect;

[0026] The structural unit I and the structural unit III are connected by... connect.

[0027] In this invention, the acid-alkali resistant composite nanofiltration membrane uses polyurea-thiourea as the separation layer, enabling the nanofiltration membrane to possess excellent acid and alkali resistance while also exhibiting high water permeability, acid permeability, and alkali permeability. Specifically, the acid-alkali resistant composite nanofiltration membrane provided by this invention can operate stably in aqueous solutions with pH = 0-14, possessing not only high water and alkali permeability but also strong acid / alkali resistance. Moreover, its preparation method is simple, making it highly promising for industrial applications.

[0028] According to the present invention, based on the total weight of the polyamine-urea separation layer, the content of structural unit I is 10-80 wt%, the content of structural unit II is 5-45 wt%, and the content of structural unit III is 15-45 wt%.

[0029] In this invention, when the contents of structural unit I, structural unit II and structural unit III in the polyurea-thiourea separation layer meet the above-mentioned range, the polyurea-thiourea separation layer has a suitable degree of crosslinking and a suitable average pore size, so that the acid and alkali resistant composite nanofiltration membrane containing the polyurea-thiourea separation layer has good acid and alkali resistance, excellent acid permeability and excellent alkali permeability.

[0030] In this invention, the contents of structural unit I, structural unit II and structural unit III in the polyurea-thiourea separation layer are determined by the XPS elemental content determination method.

[0031] Furthermore, based on the total weight of the polyurea-thiourea separation layer, the content of structural unit I is 30-70 wt%, the content of structural unit II is 10-30 wt%, and the content of structural unit III is 20-40 wt%.

[0032] According to the present invention, the polyamine is selected from at least one of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 1,3,5-triaminobenzene, melamine, piperazine, ethylenediamine, 1,2-propanediamine, 1,4-butanediamine, diethylenetriamine, tetraethylenepentamine, polyethyleneimine, and polyetheramine, preferably polyethyleneimine.

[0033] In this invention, the weight-average molecular weight of the polyethyleneimine is 1000-100000 g / mol, more preferably 2000-80000 g / mol.

[0034] According to the present invention, the polyisocyanate compound is selected from at least one of isophthalic diisocyanate, isophorone diisocyanate, 1,6-hexanediisocyanate, toluene-2,6-diisocyanate, 1,4-phenyl diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenyl diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate, and 4-chloro-6-methyl isophthalic diisocyanate, preferably 1,4-phenyl diisocyanate and / or toluene-2,4-diisocyanate.

[0035] According to the present invention, the polyisothiocyanate is at least one selected from 1,4-phenyl diisothiocyanate, 1,3-phenyl diisothiocyanate, 1,2-phenyl diisothiocyanate, 2,6-toluene diisothiocyanate, 2,3-toluene diisothiocyanate, 2,4-toluene diisothiocyanate, 2,5-toluene diisothiocyanate, 3,5-toluene diisothiocyanate, 1,6-hexane diisothiocyanate, 1,5-pentane diisothiocyanate, 1,4-butane diisothiocyanate, and 1,3-propane diisothiocyanate, preferably 1,4-phenyl diisothiocyanate and / or 1,4-butane diisothiocyanate.

[0036] According to the present invention, the average pore size of the acid and alkali resistant composite nanofiltration membrane is 0.1-0.5 nm.

[0037] According to the present invention, the molecular weight cutoff of the acid and alkali resistant composite nanofiltration membrane is 100-500 Da.

[0038] According to the present invention, the contact angle of the acid and alkali resistant composite nanofiltration membrane is 40-80°.

[0039] In this invention, when at least one of the average pore size, molecular weight cutoff, and contact angle of the composite nanofiltration membrane meets the above-mentioned range, it indicates that the separation layer of the acid and alkali resistant composite nanofiltration membrane has a suitable degree of compactness and the surface of the separation layer has excellent hydrophilicity, which can further improve the salt rejection rate, water flux, and acid and alkali resistance of the acid and alkali resistant composite nanofiltration membrane.

[0040] In a preferred embodiment of the present invention, the average pore size, molecular weight cutoff, and contact angle of the acid-alkali resistant composite nanofiltration membrane simultaneously satisfy the above-mentioned ranges of the present invention.

[0041] Furthermore, the average pore size of the acid- and alkali-resistant composite nanofiltration membrane is 0.2-0.4 nm.

[0042] Furthermore, the molecular weight cutoff is 200-400 Da.

[0043] Furthermore, the contact angle of the acid- and alkali-resistant composite nanofiltration membrane is 40-60°.

[0044] In this invention, the bottom layer and the porous support layer are not specifically limited and can be made of various existing materials with certain strength that can be used for nanofiltration and reverse osmosis membranes.

[0045] In this invention, the bottom layer is a non-woven fabric material, preferably polyester and / or polyethylene.

[0046] In this invention, the porous support layer material can be at least one of polyethersulfone, polysulfone, polyaromatic ether, polybenzimidazole, polyetherketone, polyetheretherketone, polyacrylonitrile, polyvinylidene fluoride, and polyaryletherketone.

[0047] According to the present invention, the thickness of the bottom layer, the porous support layer, and the polyurea-thiourea separation layer is not particularly limited, and can be a conventional choice in the art. However, in order to enable these three layers to play a better synergistic role and enable the resulting composite nanofiltration membrane to better combine excellent acid and alkali resistance, high water flux, desalination rate, high water permeability, acid permeability, and alkali permeability, in a preferred case, the thickness of the bottom layer is 30-150 μm, preferably 50-120 μm; the thickness of the porous support layer is 10-100 μm, preferably 30-60 μm; and the thickness of the polyurea-thiourea separation layer is 10-500 nm, preferably 50-300 nm.

[0048] A second aspect of the present invention provides a method for preparing an acid- and alkali-resistant composite nanofiltration membrane, wherein the preparation method includes the following steps:

[0049] S1. Prepare a porous support layer on the bottom layer;

[0050] S2. The membrane layer obtained in step S1 is first contacted with an aqueous phase containing polyamines, and then second contacted with an organic phase containing polyisocyanates and polyisothiocyanates. After heat treatment, the acid and alkali resistant composite nanofiltration membrane is obtained.

[0051] In this invention, the preparation method utilizes the different reactivity of polyamines, polyisocyanates, and polyisothiocyanates to form a dense polyurea-thiourea separation layer on the surface of the porous support layer during the interfacial polymerization reaction. This significantly improves water permeability and alkali permeability while ensuring the high salt rejection rate of the nanofiltration membrane. Consequently, the resulting acid and alkali resistant composite nanofiltration membrane exhibits superior acid and alkali resistance, high water flux, high desalination rate, and high water permeability, acid permeability, and alkali permeability.

[0052] In this invention, there is no particular limitation on the method for preparing the porous support layer on the bottom layer. Conventional methods in the art can be used for preparation, with phase inversion method preferred. Specifically, a polymer solution of porous support layer material is coated on one surface of the bottom layer, and the porous support layer is obtained through phase inversion.

[0053] In this invention, the phase inversion method is preferably as follows: dissolving the support layer polymer material in a solvent to obtain a polymer solution with a concentration of 10-20% by weight, degassing at 20-40°C for 10-180 min; then coating the polymer solution onto the bottom layer to obtain an initial film, and then immersing it in water at a temperature of 10-30°C for 10-60 min, thus forming the support layer polymer porous membrane through the phase inversion layer.

[0054] The solvent may be N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, dimethyl sulfoxide, etc.

[0055] According to the present invention, the polyamine is selected from at least one of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 1,3,5-triaminobenzene, melamine, piperazine, ethylenediamine, 1,2-propanediamine, 1,4-butanediamine, diethylenetriamine, tetraethylenepentamine, polyethyleneimine, and polyetheramine, preferably polyethyleneimine.

[0056] In this invention, the weight-average molecular weight of the polyethyleneimine is 1000-100000 g / mol, more preferably 2000-80000 g / mol.

[0057] According to the present invention, the polyisocyanate compound is selected from at least one of isophthalic diisocyanate, isophorone diisocyanate, 1,6-hexanediisocyanate, toluene-2,6-diisocyanate, 1,4-phenyl diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenyl diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate, and 4-chloro-6-methyl isophthalic diisocyanate, preferably 1,4-phenyl diisocyanate and / or toluene-2,4-diisocyanate.

[0058] According to the present invention, the polyisothiocyanate is at least one selected from 1,4-phenyl diisothiocyanate, 1,3-phenyl diisothiocyanate, 1,2-phenyl diisothiocyanate, 2,6-toluene diisothiocyanate, 2,3-toluene diisothiocyanate, 2,4-toluene diisothiocyanate, 2,5-toluene diisothiocyanate, 3,5-toluene diisothiocyanate, 1,6-hexane diisothiocyanate, 1,5-pentane diisothiocyanate, 1,4-butane diisothiocyanate, and 1,3-propane diisothiocyanate, preferably 1,4-phenyl diisothiocyanate and / or 1,4-butane diisothiocyanate.

[0059] According to the present invention, in the aqueous phase containing the polyamine, the content of the polyamine is 0.2-10% by weight, preferably 0.5-5% by weight.

[0060] According to the present invention, in the organic phase containing polyisocyanate and polyisothiocyanate, the content of polyisocyanate is 0.005-1% by weight, preferably 0.01-0.2% by weight; the content of polyisothiocyanate is 0.01-1% by weight, preferably 0.02-0.2% by weight.

[0061] In this invention, by controlling the content of polyamines in the aqueous phase and the content of polyisocyanates and polyisothiocyanates in the organic phase to meet the above-mentioned ranges, the prepared acid and alkali resistant composite nanofiltration membrane can have excellent acid and alkali resistance, high water flux and desalination rate.

[0062] In this invention, there is no particular limitation on the mass ratio of polyisocyanate, polyisothiocyanate and polyamine, as long as the obtained acid and alkali resistant composite nanofiltration membrane can have excellent acid and alkali resistance, high water flux and desalination rate. Preferably, the mass ratio of polyisocyanate, polyisothiocyanate and polyamine is 0.01-1:0.01-1:1, and more preferably 0.02-1:0.02-1:1.

[0063] In this invention, there is no particular limitation on the contact time between the membrane layer obtained in step S1 and the aqueous and organic phases in step S2, as long as the obtained acid and alkali resistant composite nanofiltration membrane can have excellent acid and alkali resistance, high water flux and desalination rate. Preferably, the first contact time is 5s-100s, more preferably 10s-60s; the second contact time is 10s-200s, more preferably 20s-120s.

[0064] In this invention, in step S2, the ratio of the volume of the aqueous phase to the membrane area of ​​the membrane layer obtained in step S1 is 0.05-0.5 mL / cm². 2 Preferably, it is 0.1-0.2 mL / cm 2 .

[0065] In this invention, in step S2, the ratio of the volume of the organic phase to the membrane area of ​​the membrane layer obtained in step S1 is 0.02-0.2 mL / cm². 2 Preferably, the concentration is 0.05-0.1 mL / cm³. 2 .

[0066] In this invention, the type of solvent for the organic phase is not particularly limited, as long as it can dissolve the polyisocyanate and the polybromomethyl compound. Preferably, the solvent for the organic phase is one or more of hexane, dodecane, heptane, Isopar E, Isopar G, Isopar H, Isopar L and Isopar M.

[0067] In this invention, there are no particular limitations on the heat treatment conditions, as long as the monomers can be fully polymerized and the resulting acid and alkali resistant composite nanofiltration membrane can have excellent acid and alkali resistance, high water flux and desalination rate. Preferably, the heat treatment temperature is 40-150℃, more preferably 50-120℃; the heat treatment time is 0.5-20 minutes, more preferably 1-10 minutes.

[0068] The present invention also provides a composite nanofiltration membrane prepared by the preparation method provided by the present invention.

[0069] The present invention also provides the application of the composite nanofiltration membrane described in the present invention and the composite nanofiltration membrane prepared by the preparation method described in the present invention in the field of water treatment.

[0070] The present invention will be described in detail below through embodiments.

[0071] In the following embodiments and comparative examples:

[0072] (1) The water flux of the composite nanofiltration membrane was tested by the following method: The composite nanofiltration membrane was loaded into the membrane tank and pre-pressed at 1.0 MPa for 0.5 hours. The water permeation rate of the nanofiltration membrane was measured within 1 hour at a pressure of 1.5 MPa and a temperature of 25°C, and calculated using the following formula:

[0073] J = Q / (A·t), where J is the water flux, Q is the water permeation rate (L), and A is the effective membrane area of ​​the composite nanofiltration membrane (m²). 2 ), where t is time (h).

[0074] (2) The rejection rate of the composite nanofiltration membrane for different salts was obtained by the following method: The composite nanofiltration membrane was loaded into the membrane tank and pre-pressurized at 1.0 MPa for 0.5 h. The concentration changes of salt in the initial salt source solution and permeate were measured within 1 h at a pressure of 1.5 MPa and a temperature of 25 °C, and the results were calculated using the following formula:

[0075] R = (C f -C p ) / C f ×100%, where R is the retention rate, C f C represents the concentration of salt in the original aqueous solution. p This represents the concentration of salt in the permeate.

[0076] (3) Acid resistance test of composite nanofiltration membrane: The composite nanofiltration membrane sheets were soaked in an aqueous solution containing 20% ​​HCl for 30 days, and then the changes in water flux and salt rejection rate of the composite nanofiltration membrane were tested every 5 days.

[0077] (4) Alkali resistance test of composite nanofiltration membrane: The composite nanofiltration membrane was soaked in an aqueous solution containing 20% ​​NaOH by mass for 30 days, and then the changes in water flux and salt rejection rate of the composite nanofiltration membrane were tested every 5 days.

[0078] (5) The thickness of each layer in the acid and alkali resistant composite nanofiltration membrane was determined by a spiral micrometer and a scanning electron microscope.

[0079] (6) The density of the separation layer of the acid and alkali resistant composite nanofiltration membrane is expressed by the molecular weight cutoff. The test method for the molecular weight cutoff is as follows: test the retention rate of PEG with molecular weights of 67 Da, 200 Da, 400 Da, 600 Da and 800 Da respectively. Plot the molecular weight of PEG on the x-axis and the corresponding retention rate on the y-axis. The molecular weight cutoff of the nanofiltration membrane is defined as the molecular weight corresponding to a retention rate of 90%, which is used to reflect the density of the separation layer of the nanofiltration membrane.

[0080] (7) The content of each structural unit in the separation layer of the composite nanofiltration membrane is determined by X-ray photoelectron spectroscopy of the membrane sample. Specifically, the test method is as follows: after preparing the composite nanofiltration membrane sample, the full spectrum of the X-ray photoelectron spectroscopy of the sample and the fine spectrum of nitrogen are tested respectively. The fine spectrum of nitrogen is divided into peaks to obtain the different chemical states of nitrogen in the membrane structure and its proportion in the structure. The content of each structural unit of the membrane can be calculated accordingly.

[0081] (8) The average pore size of the composite nanofiltration membrane was measured using the PEG solute transfer method, and the detailed steps are as follows:

[0082] (1) Test the retention rate of the separation membrane for PEG of different molecular sizes;

[0083] (2) Linear fitting of PEG size and retention rate in log-probability coordinate system, the PEG size corresponding to 50% retention rate is the average pore size of the separation membrane.

[0084] (9) The surface contact angle of the composite film sample was tested by the static drop method using a DSA100 surface contact angle meter manufactured by KRUSS GmbH, Germany. Before the test, the sample was dried in a vacuum oven at 60°C for 30 minutes to remove surface and internal moisture. Then, the dried film was attached to a flat glass slide with double-sided tape. The volume of each water droplet was 2 μL. The water droplet was placed on the film surface for 3 seconds and the test was performed immediately. The final contact angle was determined by taking the average value after multiple measurements.

[0085] Additionally, in the following embodiments and comparative examples:

[0086] Branched polyethyleneimine (weight average molecular weight 25000 g / mol), 1,4-phenyl diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,4-phenyl diisothiocyanate, 1,4-butane diisothiocyanate and 1,6-hexane diisothiocyanate, etc., were all purchased from Bailingwei Technology Co., Ltd., and other chemical reagents were purchased from Sinopharm Chemical Reagent Co., Ltd.

[0087] The support layer is prepared using a phase transformation method, and the specific steps are as follows:

[0088] A certain amount of polysulfone (number average molecular weight of 80,000 g / mol) was dissolved in N,N-dimethylformamide to prepare a polysulfone solution with a concentration of 18% by weight. The solution was degassed at 25°C for 120 min. Then, the polysulfone solution was coated onto a polyethylene nonwoven fabric (75 μm thick) using a doctor blade to obtain an initial film. The film was then immersed in water at 25°C for 60 min, which allowed the polysulfone layer on the surface of the polyethylene nonwoven fabric to undergo phase transformation into a porous film. Finally, after three water washes, a support layer with a total thickness of 115 μm was obtained.

[0089] Example 1

[0090] The area mentioned above is 400cm² 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 1% polyethyleneimine by weight at 25°C for 60 s, and then drained. Next, the upper surface of the support layer was contacted with 40 mL of an Isopar E solution containing 0.04% 4,4'-methylenebis(phenyl isocyanate) and 0.16% 1,4-butane diisothiocyanate by weight at 25°C for 60 s, and then drained. The membrane was then placed in an oven and heated at 70°C for 3 min to obtain the composite membrane N1. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.032:0.128:1.

[0091] The obtained composite membrane N1 was soaked in water for 24 hours, and then the water flux and salt rejection rate for different salts were measured under the conditions of 1.5 MPa and 25℃. The results are shown in Table 1. The membrane sheets were soaked in aqueous solutions of 20% HCl and 20% NaOH for 30 days, respectively. The changes in water flux and salt rejection rate of the composite nanofiltration membrane were then measured every 5 days. The results are shown in Table 1. Figure 1-2 As shown.

[0092] Example 2

[0093] The area mentioned above is 400cm² 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 3% (w / w) polyethyleneimine at 25°C for 60 s, and then drained. Next, the upper surface of the support layer was contacted with 40 mL of an Isopar E solution containing 0.08% (w / w) 4,4'-methylenebis(phenyl isocyanate) and 0.32% (w / w) 1,4-butane diisothiocyanate, and drained after 60 s at 25°C. The membrane was then placed in an oven and heated at 70°C for 3 min to obtain the composite membrane N2. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.021:0.085:1.

[0094] Example 3

[0095] The area mentioned above is 400cm² 2The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 0.5 wt% polyethyleneimine at 25°C for 60 s, and then drained. Next, the upper surface of the support layer was contacted with 40 mL of an Isopar E solution containing 0.01 wt% 4,4'-methylenebis(phenyl isocyanate) and 0.04 wt% 1,4-butane diisothiocyanate, and drained after 25°C for 60 s. The membrane was then placed in an oven and heated at 70°C for 3 min to obtain the composite membrane N3. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.016:0.064:1.

[0096] Example 4

[0097] The composite nanofiltration membrane was prepared according to the method of Example 1, except that 4,4'-methylenebis(phenyl isocyanate) was replaced with an equal mass of 1,4-phenyl diisocyanate to obtain composite membrane N4.

[0098] Example 5

[0099] The composite nanofiltration membrane was prepared according to the method of Example 1, except that 4,4'-methylenebis(phenyl isocyanate) was replaced with an equal mass of toluene-2,4-diisocyanate to obtain composite membrane N5.

[0100] Example 6

[0101] The composite nanofiltration membrane was prepared according to the method of Example 1, except that 1,4-butane diisothiocyanate was replaced with an equal mass of 1,4-phenyl diisothiocyanate to obtain composite membrane N6.

[0102] Example 7

[0103] The composite nanofiltration membrane was prepared according to the method of Example 1, except that 1,4-butane diisothiocyanate was replaced with an equal mass of 1,6-hexane diisothiocyanate to obtain composite membrane N7.

[0104] Example 8

[0105] The composite nanofiltration membrane was prepared according to the method of Example 1, except that the concentrations of 4,4'-methylenebis(phenyl isocyanate) and 1,4-butane diisothiocyanate were 0.08% by mass and 0.12% by mass, respectively, resulting in composite membrane N8. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.064:0.096:1.

[0106] Example 9

[0107] The composite nanofiltration membrane was prepared according to the method of Example 1, except that the concentrations of 4,4'-methylenebis(phenyl isocyanate) and 1,4-butane diisothiocyanate were 0.12% by mass and 0.08% by mass, respectively, to obtain composite membrane N9. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.096:0.064:1.

[0108] Example 10

[0109] The composite nanofiltration membrane was prepared according to the method of Example 1, except that the concentrations of 4,4'-methylenebis(phenyl isocyanate) and 1,4-butane diisothiocyanate were 0.16% by mass and 0.04% by mass, respectively, resulting in composite membrane N10. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.128:0.032:1.

[0110] Example 11

[0111] The composite nanofiltration membrane was prepared according to the method of Example 1, except that the concentration of 4-butane diisothiocyanate was 0.1% by mass, resulting in composite membrane N11. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.032:0.08:1.

[0112] Example 12

[0113] The composite nanofiltration membrane was prepared according to the method of Example 1, except that the concentration of 4-butane diisothiocyanate was 0.2% by mass, resulting in composite membrane N11. The mass ratio of 4,4'-methylenebis(phenyl isocyanate), 1,4-butane diisothiocyanate, and polyethyleneimine was 0.032:0.16:1.

[0114] Comparative Example 1

[0115] The area mentioned above is 400cm² 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 1% polyethyleneimine by weight at 25°C for 60 s, and then drained. Next, the upper surface of the support layer was contacted with 40 mL of an Isopar E solution containing 0.2% 4,4'-methylenebis(phenyl isocyanate) by weight at 25°C for 60 s, and then drained. The membrane was then placed in an oven and heated at 70°C for 3 min to obtain composite membrane D1. The mass ratio of 4,4'-methylenebis(phenyl isocyanate) to polyethyleneimine was 0.16:1.

[0116] Comparative Example 2

[0117] The area mentioned above is 400cm² 2 The upper surface of the polysulfone support layer was contacted with 50 mL of an aqueous solution containing 1% polyethyleneimine by weight at 25°C for 60 s, and then drained. Next, the upper surface of the support layer was contacted with 40 mL of an Isopar E solution containing 0.2% 1,4-butane diisothiocyanate by weight at 25°C for 60 s, and then drained. The membrane was then placed in an oven and heated at 70°C for 3 min to obtain composite membrane D2. The mass ratio of 1,4-butane diisothiocyanate to polyethyleneimine was 0.16:1.

[0118] The thickness of each layer of the composite nanofiltration membrane, the molecular weight cutoff, average pore size, contact angle, and the content of each structural unit in the polyamine-urea separation layer in the examples and comparative examples are shown in Table 1.

[0119] Table 1

[0120]

[0121]

[0122] Table 1 (continued)

[0123] Structural unit I / wt% Structural Unit II / wt% Structural Unit III / wt% Example 1 52.0 15.6 32.4 Example 2 56.8 17.4 25.8 Example 3 49.8 12.4 37.8 Example 4 52.6 18.9 28.5 Example 5 49.7 14.7 35.6 Example 6 48.9 13.8 37.3 Example 7 51.3 17.8 30.9 Example 8 50.9 20.4 28.7 Example 9 50.3 23.5 26.2 Example 10 51.0 26.9 22.1 Example 11 53.3 19.2 27.5 Example 12 48.3 15.2 36.5 Comparative Example 1 56.9 43.1 0 Comparative Example 2 59.2 0 40.8

[0124] The water flux, sodium chloride rejection rate, sodium sulfate rejection rate, magnesium sulfate rejection rate, sodium hydroxide rejection rate, acid resistance, and alkali resistance of the composite membranes in the examples and comparative examples were tested, and the results are shown in Tables 2 and 3, respectively.

[0125] Table 2

[0126]

[0127]

[0128] As shown in Table 2, compared with the pure polyurea structure, the introduction of the thiourea structure not only improved the membrane's rejection rate for salt ions but also effectively increased the membrane's water flux. On the other hand, the polyurea-thiourea nanofiltration membrane showed a decrease in the rejection rate of sodium hydroxide, indicating that the thiourea group has a better affinity for water and alkali, which is conducive to the permeation of water molecules and hydroxide ions. At the same time, its dense cross-linked network structure effectively hinders the permeation of salt ions.

[0129] Table 3

[0130]

[0131] As shown in Table 3, the polyurea-thiourea nanofiltration membrane exhibits superior acid and alkali stability compared to both pure polyurea and pure polythiourea nanofiltration membranes, indicating that the urea-thiourea structure has better acid and alkali resistance.

[0132] Depend on Figure 1-2 It can be seen that the composite membrane with polyurea-thiourea as the separation layer exhibits excellent stability in aqueous solutions of 20% HCl and 20% NaOH. Even after immersion in these extremely acidic or alkaline solutions for 30 days, the rejection rate of MgSO4 remains above 90%-95%. The water flux increases significantly with increasing immersion time, indicating that the polyurea-thiourea cross-linked structure swells in extremely acidic or alkaline solutions.

[0133] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. An acid- and alkali-resistant composite nanofiltration membrane, characterized in that, The composite nanofiltration membrane comprises, in sequence, a bottom layer, a porous support layer, and a polyurea-thiourea separation layer; The polyurea-thiourea separation layer includes structural unit I from polyamines, structural unit II from polyisocyanate compounds, and structural unit III from polyisothiocyanates; Wherein, structural unit I and structural unit II are connected by connect; The structural unit I and the structural unit III are connected by... connect; Based on the total weight of the polyurea-thiourea separation layer, the content of structural unit I is 10-80 wt%, the content of structural unit II is 5-45 wt%, and the content of structural unit III is 15-45 wt%. The acid and alkali resistant composite nanofiltration membrane has an average pore size of 0.2-0.4 nm; The contact angle of the acid and alkali resistant composite nanofiltration membrane is 40-60°.

2. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1, wherein, Based on the total weight of the polyurea-thiourea separation layer, the content of structural unit I is 30-70 wt%, the content of structural unit II is 10-30 wt%, and the content of structural unit III is 20-40 wt%.

3. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The polyamine is selected from at least one of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 1,3,5-triaminobenzene, melamine, piperazine, ethylenediamine, 1,2-propanediamine, 1,4-butanediamine, diethylenetriamine, tetraethylenepentamine, polyethyleneimine, and polyetheramine.

4. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The polyisocyanate compound is selected from at least one of the following: isophthalic diisocyanate, isophorone diisocyanate, 1,6-hexanediisocyanate, toluene-2,6-diisocyanate, 1,4-phenyl diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenyl diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate, and 4-chloro-6-methyl isophthalic diisocyanate.

5. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The polyisothiocyanate is at least one selected from 1,4-phenylene diisothiocyanate, 1,3-phenylene diisothiocyanate, 1,2-phenylene diisothiocyanate, 2,6-toluene diisothiocyanate, 2,3-toluene diisothiocyanate, 2,4-toluene diisothiocyanate, 2,5-toluene diisothiocyanate, 3,5-toluene diisothiocyanate, 1,6-hexane diisothiocyanate, 1,5-pentane diisothiocyanate, 1,4-butane diisothiocyanate, and 1,3-propane diisothiocyanate.

6. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The acid and alkali resistant composite nanofiltration membrane has a molecular weight cutoff of 100-500 Da.

7. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The acid and alkali resistant composite nanofiltration membrane has a molecular weight cutoff of 200-400 Da.

8. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The thickness of the bottom layer is 30-150 μm.

9. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The thickness of the bottom layer is 50-120 μm.

10. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The thickness of the porous support layer is 10-100 μm.

11. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The thickness of the porous support layer is 30-60 μm.

12. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The thickness of the polyurea-thiourea separation layer is 10-500 nm.

13. The acid- and alkali-resistant composite nanofiltration membrane according to claim 1 or 2, wherein, The thickness of the polyurea-thiourea separation layer is 50-300 nm.

14. A method for preparing the acid- and alkali-resistant composite nanofiltration membrane according to any one of claims 1-13, characterized in that, The preparation method includes the following steps: S1. Prepare a porous support layer on the bottom layer; S2. The membrane layer obtained in step S1 is first contacted with an aqueous phase containing polyamines, and then second contacted with an organic phase containing polyisocyanates and polyisothiocyanates. After heat treatment, the acid and alkali resistant composite nanofiltration membrane is obtained.

15. The preparation method according to claim 14, wherein, The polyamine is selected from at least one of m-phenylenediamine, p-phenylenediamine, o-phenylenediamine, 1,3,5-triaminobenzene, melamine, piperazine, ethylenediamine, 1,2-propanediamine, 1,4-butanediamine, diethylenetriamine, tetraethylenepentamine, polyethyleneimine, and polyetheramine.

16. The preparation method according to claim 14, wherein, The polyisocyanate compound is selected from at least one of the following: isophthalic diisocyanate, isophorone diisocyanate, 1,6-hexanediisocyanate, toluene-2,6-diisocyanate, 1,4-phenyl diisocyanate, toluene-2,4-diisocyanate, 4,4'-methylenebis(phenyl isocyanate), 1,3-phenyl diisocyanate, 3,3'-dichloro-4,4'-diisocyanate biphenyl, dicyclohexylmethane-4,4'-diisocyanate, trimethylhexamethylene diisocyanate, L-lysine-ethyl ester-diisocyanate, 1,4-cyclohexyl diisocyanate, and 4-chloro-6-methyl isophthalic diisocyanate.

17. The preparation method according to claim 14, wherein, The polyisothiocyanate is at least one selected from 1,4-phenylene diisothiocyanate, 1,3-phenylene diisothiocyanate, 1,2-phenylene diisothiocyanate, 2,6-toluene diisothiocyanate, 2,3-toluene diisothiocyanate, 2,4-toluene diisothiocyanate, 2,5-toluene diisothiocyanate, 3,5-toluene diisothiocyanate, 1,6-hexane diisothiocyanate, 1,5-pentane diisothiocyanate, 1,4-butane diisothiocyanate, and 1,3-propane diisothiocyanate.

18. The preparation method according to claim 14, wherein, The content of the polyamine in the aqueous phase containing the polyamine is 0.2-10% by weight.

19. The preparation method according to claim 14, wherein, The content of the polyamine in the aqueous phase containing the polyamine is 0.5-5% by weight.

20. The preparation method according to claim 14, wherein, In the organic phase containing polyisocyanates and polyisothiocyanates, the content of the polyisocyanates is 0.005-1% by weight; the content of the polyisothiocyanates is 0.01-1% by weight.

21. The preparation method according to claim 14, wherein, In the organic phase containing polyisocyanates and polyisothiocyanates, the content of the polyisocyanates is 0.01-0.2% by weight; the content of the polyisothiocyanates is 0.02-0.2% by weight.

22. The preparation method according to claim 14, wherein, The mass ratio of the polyisocyanate, the polyisothiocyanate, and the polyamine is 0.01-1:0.01-1:

1.

23. The preparation method according to claim 14, wherein, The mass ratio of the polyisocyanate, the polyisothiocyanate, and the polyamine is 0.02-1:0.02-1:

1.

24. The preparation method according to claim 14, wherein, The duration of the first contact is 5s-100s.

25. The preparation method according to claim 14, wherein, The duration of the first contact is 10s-60s.

26. The preparation method according to claim 14, wherein, The second contact time is 10s-200s.

27. The preparation method according to claim 14, wherein, The second contact time is 20s-120s.

28. The preparation method according to claim 14, wherein, The heat treatment conditions include: a heat treatment temperature of 40-150℃ and a heat treatment time of 0.5-20 minutes.

29. The preparation method according to claim 14, wherein, The heat treatment conditions include: a heat treatment temperature of 50-120℃ and a heat treatment time of 1-10 minutes.

30. An acid- and alkali-resistant composite nanofiltration membrane prepared by any one of claims 14-29.

31. The application of the acid and alkali resistant composite nanofiltration membrane according to any one of claims 1-13 and 30 in the field of water treatment.

Citation Information

Patent Citations

  • Method for efficiently producing low-carbon olefin from oxygen-containing compound

    CN113509893A

  • Solvent and acid stable membranes, methods of manufacture thereof and methods of use thereof inter alia for separating metal ions from liquid process streams

    US9943811B2

  • Acid / alkali-resistant composite nanofiltration membrane as well as preparation method and application thereof

    CN113509839A

  • Membranes and methods of treating membranes

    US20070039874A1